ON NUMEROV METHOD FOR SOLVING FOURTH ORDER ORDINARY DIFFERENTIAL EQUATIONS (FUDMA JOURNAL OF SCIENCES, 2021)
In this work, a fourth order ODE of the form  is transformed into a system of differential equations that is suitable for solution by means of Numerov method. The obtained solutions are compared with the exact solutions, and are shown to be very effective in solving both initial and boundary value problems in ordinary differential equations.
Keywords: Numerov’s method, Runge-Kutta method, Schrodinger equation, Second order, Initial value problems